The Blackwell companion to Paul - Westerholm, Stephen (Blackwell companions to religion, 2011)
Front Matter -- Introduction / Stephen Westerholm -- Paul and Christian Origins. Pauline Chronology / Rainer Riesner -- Paul and the Macedonian Believers / Todd D Still -- Paul and the Corinthian Believers / Craig S Keener -- Paul and the Galatian Believers / Stephen Chester -- Paul and the Believers of Western Asia / John Paul Heil -- Paul and the Roman Believers / Beverly Roberts Gaventa -- The Pastoral Epistles / I Howard Marshall -- The Portrait of Paul in Acts / Stanley E Porter -- The Gospel according to St. Paul / James D G Dunn -- Paul and Scripture / J Ross Wagner -- Paul's Christology / Simon J Gathercole -- Paul, Judaism, and the Jewish People / John M G Barclay -- Paul and the Law / Arland J Hultgren -- The Text of the Pauline Corpus / Dirk Jongkind -- Rhetoric in the Letters of Paul / Jean-No︠l Aletti -- The Social Setting of Pauline Communities / Gerd Theissen -- Women in the Pauline Churches / Margaret Y MacDonald -- Paul and Empire / N T Wright -- Readers of Paul. Marcion / Heikki R̃is̃nen -- Origen / Peter Widdicombe -- Chrysostom / Christopher A Hall -- Augustine / Lewis Ayres -- Aquinas / Matthew Levering -- Luther / Mickey L Mattox -- Calvin / Anthony N S Lane -- John and Charles Wesley / John R Tyson -- Barth / Richard E Burnett -- Recent Continental Philosophers / P Travis Kroeker -- Jewish Readings of Paul / Daniel R Langton -- Orthodox Readings of Paul / Theodore G Stylianopoulos -- African Readings of Paul / Grant LeMarquand -- The Legacy of Paul. Art / Robin M Jensen -- Literature / David Lyle Jeffrey -- Christian Theology: Sin and the Fall / Marguerite Shuster -- Christian Theology: The Spirit / Ralph Del Colle -- Christian Theology: Ethics / Gilbert Meilaender -- Christian Theology: The Church / Nicholas M Healy -- Index